Recognition of the authority of foreign criminal law in the light of UAE law and the provisions of international conventions: الاعتراف بحجية الحكم الجنائي الأجنبي على ضوء القانون الإماراتي وأحكام الاتفاقيات الدولية (المجلة العربية للعلوم و نشر الأبحاث, 2017)
Basic principle is that the criminal verdict in a particular state- according to regional base criminal law- does not have any impact beyond the borders of this state, is that the talk Fiqh began to call the necessity to recognize the executive force of criminal judgment foreigner on the territory of the State, especially with the increase in organized crime activities and the difficulty of detection ,, The research aims to show the extent of recognition of the legislator Emirati all of the negative effects and the effects of positive foreign criminal judgment, according to comparative approach between the UAE law and relevant international conventions, showed results that the legislator UAE has admitted strongly res judicata criminal rule of foreign matter in order to avoid trial person per incident twice, and also acknowledged the executive force of criminal judgment foreigner on the territory of the State provided there is an international agreement between the UAE and foreign countries, including the recognition of foreign rule this impact and the condition of reciprocity, it concluded Find out the importance of the recognition of foreign rule executive strongly as prescribed by the penalties and confiscated private necessity for international cooperation in the fight against organized crime penalty.